Vakfname-i Rub’-i Reşîdî : el-Vakfiyyetü’r-Reşîdiyye bi Hatti’l-Vakıf fî Beyani Şeraiti Umuri’l-Vakfi’l-Mesarif = Al-Waqfiyyah ar-Rashidiyyah the act for the pious foundation : facsimile of the original fourteenth-century document drawn by himself and by his order - Reşîdüddîn Fazlullah b. Ebî’l-Hayr b. ‘Âlî el-Hemedanî. (Tahran)
22, [386] s.